Roles in school bullying and well-being: An analysis of justice perceptions and perceived social support as mediators - Garcia, D´Jamila Rossana da Silva (2018)
Bullying incidents are common in schools and they have negative and widespread effects, namely on the mental and physical health of those who are more directly involved. In this thesis, we aim to expand the literature by exploring the relationship between bullying and well-being and by providing a theoretical framework that can explain this relationship. We developed three cross-sectional studies with adolescents and young adults in an educational setting. In Study 1 (n = 380), we proposed to analyze the relationship between bullying and the well-being of participant roles in bullying (victims, bullies, assistants, reinforcers, defenders and outsiders). Study 2 (n = 202) is an extension of Study 1 in which we investigated bullying behaviors retrospectively. In Study 3 (n = 565) we explored justice perceptions and perceived social support as mediators in the relationship between bullying and well-being of victims, bully-victims, bullies and non-involved students. We argued that these mediators were indicators of the threat that bullying poses to the need to belong and can help explain the relationship between bullying and well-being. Our results showed that bullying is negatively associated with well-being in the short and long-term. In the short-term, effects are experienced primarily by victims (and bully-victims). However, in the long-term, both victims and bullies experience the negative effects of bullying. The results also showed that victims and bully-victims experienced deterioration in their justice perceptions and perceived social support. We interpreted these results as empirical support for our argument. We discussed our results regarding their potential contribution to prevention and intervention efforts, and to the literature that establishes bullying as a serious social problem with multilayered consequences.